Effect of Rice Straw Compost and Water Regimes on Growth Performance of Tomato (Lycopersicum Esculentum L.) - Ali, Hassan Ibrahim (2005)
The use of low technological agronomic manipulations, such as composted organic amendments and new irrigation techniques can contribute positively in water use efficiency and agriculture sustainability under limited resources. The objective of this study was to evaluate the effect of rice straw compost on plant physiological status, growth, yield, fruit quality and water use of tomato grown under protected environment in humid climatic conditions of Malaysia, using soilless and soil mixture media in combination with water regimes either by withholding or by using partial rootzone drying (PRD) technique. Rice straw compost treated with chicken manure (2:1) using static aeration pile system has suitable physiochemical properties ranging within compost standards. The use of rice straw compost in combination with a peat based vegetable transplant media, especially with 25%and 50% compost mixture was observed to provide a more appropriate medium compared to rice straw iv compost or peat mix alone for production of tomato seedlings and showed improvement in all growth parameters. The addition of rice straw compost at 30%, significantly increased plant dry biomass, fruit diameter, yield and water use efficiency (WUE) in both media, whereas the water deficit significantly decreased these parameters in most of the treatments. The addition of rice straw compost, however, had opposite effects on the two media in terms of total organic matter. The total organic matter significantly increased in the soil mixture, while it significantly decreased in the soilless media. The results indicated that the soilless media was not affected by the stress regime in most of these parameters. This suggests that the soilless media increased the water holding capacity and other physical properties better than the soil mixture. The results also indicated that media drying decreased leaf water potential, stomatal conductance, as well as, plant dry biomass, in addition to increasing proline accumulations, with slight differences between the different growth media. PRD, on the other hand, was obsereve to significantly reduce leaf expansion, plant leaf area and stomatal conductance in both media, but severely with soil mixture, whereas proline and sugars namely fructose, glucose and sucrose, were dramatically increased in the leaf especially with soil mixture. Stomatal conductance, leaf expansion and proline accumulation, however, significantly correlated with media drying. Dry matter partitioning showed a significant reduction in total dry matter and plant dry shoot weight with v PRD, but significantly increased root to shoot ratio with no significant differences in plant dry root weight. WUE increased significantly with PRD in both media. The use of soilless media resulted in a significant increase in all biological parameters. Yield was also affected with PRD in both media; there was significant interaction between the two media and irrigation regime. However, there was no significant reduction in marketable yield due to PRD in soilless media. This suggests that PRD application could be effective in soilless media. PRD significantly improved fruit carbohydrates and other fruit quality indices